2018
DOI: 10.1371/journal.pone.0199928
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance trends in fecal Salmonella isolates from northern California dairy cattle admitted to a veterinary teaching hospital, 2002-2016

Abstract: Nontyphoidal Salmonella infections contribute to approximately 1.2 million annual illnesses in the United States. Historical and recent outbreaks have been associated with dairy products, ground beef, and direct contact with cattle. Salmonella antimicrobial resistance (AMR) is a serious concern that can reduce successful treatment of infections, increasing recovery time, medical costs, and mortality rates in humans and animals. This highlights the need to track AMR in Salmonella isolated from cattle to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In this study, S. Typhimurium was isolated from calves with diarrhoea, septicaemia and mortality, as reported in previous works [7,21]. The serotype S. Anatum was only isolated from faecal samples from only one dairy farm (Table S1).…”
supporting
confidence: 67%
“…In this study, S. Typhimurium was isolated from calves with diarrhoea, septicaemia and mortality, as reported in previous works [7,21]. The serotype S. Anatum was only isolated from faecal samples from only one dairy farm (Table S1).…”
supporting
confidence: 67%
“…A total of 110 Salmonella isolates were selected for qPCR analysis from a collection of 242 Salmonella isolates recovered from 9162 bovine fecal samples submitted to the University of California, Davis William R. Pritchard VMTH microbiology laboratory between January 1, 2002 and December 31, 2016 as detailed previously ( Davidson et al, 2018 ). Sixty-eight isolates were recovered from dairy cattle exhibiting clinical signs of Salmonella infection, while 42 isolates were recovered from asymptomatic dairy cattle through the VMTH Infectious Disease Control (IDC) program.…”
Section: Methodsmentioning
confidence: 99%
“…Illnesses that were once easily treatable with antibiotics are becoming more difficult to cure due to the emergence of resistance to present generation drugs. Rapid annual development of antibiotic resistance in nontyphoidal Salmonella serovars has become a significant problem (Angelo et al, 2016;Davidson et al, 2018). In a similar study aimed at examining the prevalence and antimicrobial resistance of Salmonella isolates from broiler chickens, pigs and their associated meat products revealed that the multidrug resistance was 34% in Thailand and 52% in Cambodia.…”
Section: Presence Of Antimicrobial Resistant Genesmentioning
confidence: 99%
“…Despite to the increasing incidence of ciproflioxacin resistant Salmonella in some countries (Threlfall et al, 2002;Medalla et al, 2013) several studies have found that there is a decreasing tendency of developing resistance in Salmonella against few antibiotics and it is in agreement with the findings of the current study. For instance, Davidson et al, (2018) have found no isolate resistant to ciprofloxacin among total of 242 Salmonella isolates. In other studies too, monitoring Salmonella isolates have shown that there was no resistance to ciprofloxacin and nalidixic acid (Cummings et al, 2013;Davidson et al, 2018).…”
Section: Presence Of Antimicrobial Resistant Genesmentioning
confidence: 99%
See 1 more Smart Citation